Comprehensive analysis of lncRNAs and mRNAs revealed potential participants in the process of avian reovirus infection - Zhang, Shaqiu; Li, Jinkang; Wang, Mingshu; Jia, Renyong; Chen, Shun; Liu, Mafeng; Zhu, Dekang; Zhao, Xinxin; Wu, Ying; Yang, Qiao; Huang, Juan; Ou, Xumin; et al. (Frontiers in Microbiology, 2025)
Avian reovirus (ARV), a double-stranded RNA virus, frequently induces immunosuppression in poultry, leading to symptoms such as irregular bleeding and spleen necrosis in infected ducks. Since 2017, the morbidity and mortality rates associated with ARV infection in poultry have been on the rise, progressively emerging as a significant viral disease impacting the duck farming industry in China. In our study, we collected duck embryo fibroblasts 18 h post-infection with ARV and conducted transcriptome sequencing analysis. The analysis revealed that 3,818 mRNA expressions were up-regulated, 4,573 mRNA expressions were down-regulated, 472 long noncoding RNAs (LncRNAs) were up-regulated, and 345 lncRNAs were down-regulated. We employed qRT-PCR to validate the sequencing results, confirming their accuracy. The transcriptome data indicated significant upregulation of the PARP9, TLR7, TRIM33, and ATG5 genes, suggesting their potential involvement in ARV infection. Notably, our study identified a novel functional lncRNA, MSTRG.9284.1 (It was named linc000889 in the present study), which inhibits the replication of ARV at the transcriptional, translational levels and viral titer. Overall, this study has identified numerous ARV-induced differentially expressed mRNAs and lncRNAs, including the functional lncRNA linc000889 that inhibits ARV replication. This discovery provides new insights into the mechanisms of ARV infection and may contribute to the development of new prevention and treatment strategies.